Clinical characteristics of responders to treatment with tolvaptan in patients with acute decompensated heart failure: Importance of preserved kidney size. Issue 2 (February 2016) - Toda, Hironobu; Nakamura, Kazufumi; Nakahama, Makoto; Wada, Tadashi; Watanabe, Atsuyuki; Hashimoto, Katsushi; Terasaka, Ritsuko; Tokioka, Koji; Nishii, Nobuhiro; Miyoshi, Toru; Kohno, Kunihisa; Kawai, Yusuke; et al.
Abstract: Background: Recent clinical trials have demonstrated the efficacy of short-term treatment with tolvaptan, an oral vasopressin V2 receptor antagonist, in patients with heart failure. However, the response to tolvaptan varies among patients. The aim of this study was to determine factors associated with response to tolvaptan in patients with acute decompensated heart failure (ADHF). Methods: The Tolvaptan Registry, a prospective, observational, multicenter cohort study performed in Japan, aims to determine factors affecting the responsiveness of tolvaptan in patients with ADHF. We enrolled ADHF patients treated with tolvaptan and they were divided into two groups: responders and non-responders. Responders were defined as subjects who met all of the following three conditions: (1) increasing urine volume during a 24-hour period after the start of tolvaptan treatment; (2) improvement in New York Heart Association functional class; and (3) decrease in cardiothoracic ratio assessed by chest X-ray on day 3 of tolvaptan administration. Results: Among the 114 patients, treatment with tolvaptan improved three conditions of heart failure in more than half of all the cohorts (71 patients, 62%). As for baseline characteristics, estimated glomerular filtration rate, urine osmolality, and kidney size were significantly greater in responders than in non-responders. Multivariate logistic analysis revealed that kidney size was independently associated with responders (odds ratio: 1.083, p = 0.001, 95% confidence interval 1.031–1.137). Conclusions: The main clinical characteristic of responders to treatment with tolvaptan is that kidney size is preserved.